Study on dynamic response characteristics of jointed coal mass under impact load - Jianfeng LIU (Meikuang Anquan)
Based on the similarity theorem, the material ratio of similar coal body is determined, and the single-layer thin-plate coal body is prepared by pouring. The multi-layered combined coal mass model with three joint structures is prepared by using the method of dolomite glue cementation. Using the self-developed true triaxial drop hammer impact test device, it is found that the jointed coal body produces circumferential cracks and radial cracks and produces petal-like fragments through the drop hammer impact test. To clarify the formation mechanism of coal failure characteristics, this study laid multiple strain gauges on the surface of the combined coal body to monitor the strain response characteristics of the measuring points in all directions on the surface of the coal body. It was found that during the impact process, the radial position of the first layer of the coal body first produced compressive strain and then tensile strain, and the circumferential position first produced tensile strain and then compressive strain. The axial position of the side impact of the coal body mainly produces compressive strain, and the radial position of the side impact mainly produces tensile strain. To further clarify the response characteristics of the jointed multi-layer coal body during the drop hammer impact process, the domestic discrete element software Matdem is used to construct a drop hammer impact discrete element model. The calculation model completely reproduces the propagation process of the spherical wave formed by the drop hammer impact in the jointed multi-layer composite coal body, and extracts the variation law of \begin{document}$ {σ }_{{\textit z}} $\end{document} inside the coal body. Combined with the stress wave propagation mechanism, it is clear that the elastic unloading wave formed by unloading during the whole process of dropping hammer impact failure of multi-layer coal body catches up with the pre-plastic loading carrier formed during the dropping hammer loading process. The unloading process leads to the formation of annular cracks in the combined coal body, which leads to the failure characteristics of the petal-shaped fragments formed by the intersection of the annular cracks and the radial cracks and the evolution characteristics of the broken coal body.